Antibiotic resistance pattern of Staphylococcus aureus infections in children - Kumar K., Senthil; Kumar C., Ajith Brabhu (International Journal of Contemporary Pediatrics, 2019)
Background: Methicillin resistant Staphylococcus aureus (MRSA) is endemic in India and is a dangerous pathogen for hospital acquired infections. Analysing antibiotic susceptibility pattern of Staphylococcus helps us to overcome the therapeutic difficulties created by the rising anti-microbial resistant bacteria and guide us in choosing appropriate antibiotics. Hence, this study was conducted. Methods: Children with confirmed S. aureus infection between the age group of 0-12 years were classified into MSSA and MRSA subgroups. Isolates were identified as S. aureus using standard microbiological methodologies at diagnostic bacteriology laboratory, in the Microbiology department. Basic demographic variables and antibiotic resistance patterns were compared between MRSA and MSSA subgroups. Results: Majority of S. aureus were isolated from pus followed by blood culture. Prevalence of community acquired MRSA in present study (80%, with 95% CI from 68.56% to 91.44%) was significantly higher when compared to another studies (p value=0.004). Resistance to gentamicin and ciprofloxacin among the MRSA isolates was more than that in methicillin sensitive S. aureus (MSSA) (P<0.001). Conclusions: It is prudent to include MRSA coverage in empirical antibiotic regimens in settings where a significant proportion of patients hospitalized for S. aureus infection have MRSA.